24‐epibrassionlide improves photosynthetic response of Rhododendron delavayi to drought. (23rd October 2020) - Cai, Yan‐Fei; Peng, Lv‐Chun; Li, Shi‐Feng; Zhang, Lu; Xie, Wei‐Jia; Song, Jie; Wang, Ji‐Hua
Abstract : Rhododendron delavayi is an alpine evergreen ornamental plant with strong tolerance to drought stress. Brassinosteroids are promising agents for alleviating the negative effects of drought on plants, but the mechanism by which BRs induce plant resistance to drought is not well understood. The present study investigated the effects of exogenous spray of 24‐epibrassionlide (EBR) at different concentrations (0 1 mg l −1 ) on the physiological response of R. delavayi to drought caused by no watering for 10 days. With the increase in EBR concentration, net photosynthetic rate, stomatal conductance, transportation rate, light saturated photosynthetic rate, light compensation point, light saturation point, excitation energy capture efficiency of reaction center, actual photochemical efficiency of photosystem II (PSII), photochemical quenching and electron transport rate significantly increased, but there were no significant effects on photosynthetic pigment content. These results suggested that the EBR‐induced improvement in CO2 assimilation under drought was mainly related to stomatal and non‐stomatal factors, and partially attributed to the increased photochemical efficiency of PSII. In addition, the leaf water potential increased with the increase in EBR concentration, while the malondialdehyde, superoxide dismutase, catalase, proline and soluble protein decreased. The results suggested EBR application partially alleviated the negative effect of drought on R. delavayi by improving water relations and decreasing lipid peroxidation and reactive oxygen species production. We concluded that exogenous application of EBR improved photosynthesis and alleviated the negative effects of drought‐induced membrane peroxidation and severe oxidative stress.